Galerie Wanda Reiff Maastricht : Tentoonstellingen 1991. - Galerie Wanda Reiff, Maastricht (Maastricht : Galerie Wanda Reiff, 1991)
Katase, Kazuo ; Claessen, Wim ; Mostard, Yvonne ; Parmiggiani, Claudio ; Schouten, Lydia ; Slits, Ton ; Vugs, Joop ; Visch, Henk ; Wehrens, Peter ; Bömmels, Peter ; Dahn, Walter ; Dokoupil, Jiri Georg ; Messager, Annette ; Sherman, Cindy ; Trockel, Rosemarie ; Garcia Sevilla, Ferran ; Saiz, Manuel ; Lavier, Bertrand
Nederlands & Engels
boek